IFPRI guiding principles for policy research and policy advice - International Food Policy Research Institute (International Food Policy Research Institute, 2006)
IFPRI's research is guided by a mission of generating knowledge to reduce poverty, hunger, and malnutrition. IFPRI's strategy describes the Institute's programs and its research and capacity strengthening goals. In pursuit of these goals, IFPRI research staff should adhere to a series of guiding principles which are enumerated in this paper.